Aspects of Intertextuality in the Works of the ‘Stalowa Wola Generation’ (Eugeniusz Knapik, Andrzej Krzanowski, Aleksander Lasoń) - Kiwała, Kinga (Interdisciplinary Studies in Musicology, 2019)
In the panorama of Polish music of the 2nd half of the 20th century the works of Silesian composers stand out. They were born in 1951 and thus they are referred to as the ‘Generation 51’ or the ‘Stalowa Wola Generation’ (from the place of their debut at the Festival ‘Young Musician for the Young City’ in Stalowa Wola in 1976): Eugeniusz Knapik, Aleksander Lasoń and Andrzej Krzanowski. They constituted the first generational phenomenon of such significance in Polish music since the debut of ‘Generation 33’ (Krzysztof Penderecki, Henryk Mikołaj Górecki and others). The musical style of these young authors was in tune with the Polish popular phenomenon of the 1970s of ‘New Romanticism’, consisting in a return to certain artistic and aesthetic values lost in modernism and avant-garde. One of the distinguishing features of Knapik’s, Lasoń’s and Krzanowski’s work is the application of various ‘intertextual strategies’ – quotations, allusions, and clear references to more or less specific musical traditions. In the works of ‘Generation 51’ composers, these strategies have a certain superior ‘axiological sense’ (Władysław Stróżewski), which is far from a purely ludic, postmodernist play on conventions and texts. The aim of the text is a review and an attempt to interpret those strategies. A methodological reference point will be the semantic analyses of possible intertextual references performed by Mieczysław Tomaszewski and Stanisław Balbus.